Treatment of Class II Div 2 Malocclusion using PowerScope: A Case Report - Agarwal, Luv; Singh, Kamlesh; Tandon, Ragni (Orthodontic Journal of Nepal, 2018)
Correction of skeletal Class II malocclusion has become a major challenge for orthodontists. Class II jaw discrepancies characterized by mandibular deficiency are treated with fixed functional appliances when there is no active growth present. This case report illustrates the application of PowerScope in 16 years young adolescent male having skeletal Class II Div 2 with mandibular deficiency who was reported with forwardly and irregularly placed upper front teeth with closed bite. The case was treated initially with MBT 0.022” prescription followed by PowerScope. Successful results were obtained with a substantial improvement in facial profile, skeletal jaw relationship and overall aesthetic appearance. PowerScope produced a significant forward movement of mandible which obliterated the need of extractions